Temporal-spacial relationships between facial stimulation-evoked filed potential responses in mouse cerebellar granular layer and molecular layer. (13th July 2019) - Ma, Chang; Lu, Di; Cao, Li-Xin; Bing, Yan-Hua; Chu, Chun-Ping; Qiu, De-Lai
Highlights: Facial stimulation evoked successively field potentials in cerebellar ML and GL. The field potentials express an excitatory component, N1 and an inhibitory component, P1. Latencies of P1 in both GL and ML were similar regardless the relative recording sites in GL. Blocking either AMPA or GABAA receptors abolished P1 in both ML and GL. Abstract: The cerebellum receives sensory inputs from mossy fiber-granule cell or climbing fiber pathways, and generates motor-related outputs. However, the temporal and special mechanism of the sensory information processing in cerebellar cortex is still unclear. Therefore, we here investigated the temporal-spacial mechanism between the facial stimulation-evoked field potential responses in granular layer (GL) and molecular layer (ML), by duo-electrophysiological recording technique and pharmacological methods in urethane-anesthetized mice. Our results showed that air-puff stimulation of ipsilateral whisker pad evoked successively field potential responses in GL and ML. The field potential response in GL exhibited a strong excitatory component (N1) followed by an inhibitory component (P1), while the field potential response in ML exhibited a tiny excitatory component (N1) followed by strong inhibitory component (P1). The latency of N1 was decreased with the increase of recording depth in ML, and it was the shortest in GL. Notably, the latencies of P1 in GL and ML were similar regardless the relative recording sites. Furthermore, blocking α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor-mediated parallel fiber excitatory inputs by application of AMPA receptor antagonist, NBQX prevented P1 in both ML and GL. Moreover, application of GABAA receptors antagonist, gabazine simultaneously abolished P1 in both ML and GL. These results indicate that the facial stimulation evoked a simultaneous GABAergic inhibition in both ML and GL via mossy fiber-GC-parallel fiber pathway, suggesting that the sensory stimulation simultaneously evoked excitation of molecular layer interneurons (MLIs) and GL Golgi cells in cerebellar cortex.